Occurrence of Acanthosis Nigricans, A Benign Condition or Associated with Systemic Disease. A Case-Control Study - Acharya, R.; Rijal, A. (Nepal Journal of Dermatology, Venereology & Leprology, 2016)
Background: Acanthosis nigricans (AN), a common cutaneous finding, characterized by hyperpigmentation and velvety hyperplasia of the epidermis affecting flexures. Its exact prevalence varies according to age, race, degree of obesity and endocrinopathy. Objectives: Though previous studies have identified AN as marker of hyperinsulinemia and its common association with obesity, this study was done to see if AN occurs as benign condition or has any underlying disease and also to identify the possible risk factors associated with it. Material and methods: Clinically diagnosed cases of AN (n=55) were included with equal number of healthy control. Height, weight, abdominal circumference, body mass index (BMI), level of Blood Sugar and Lipids were measured. Comorbidities were defined as hypertension: Blood pressure ≥ 140/90 mmHg; Diabetes mellitus: Fasting Blood sugar (FBS) >125mg/dl, Post prandial >160mg/dl, Obesity grading as per WHO criteria and Metabolic Syndrome: ATP III criteria. Data were assessed using univariate analysis with crude odds ratio and 95% confidence intervals. Variables with p-value ≤ 0.05 were tested in multivariate model. Results: Of 55 cases of AN, 94.5% had one or more underlying disease. Obesity (89.09%) was the most common associated condition followed by dyslipidemia (87.2%), metabolic syndrome (56%), hypertension (38.18%), diabetes (18.8%) and hypothyroidism (14.54%). There was a strong association of AN with increased waist circumferences (OR 7.93), BMI (OR 6.8), metabolic syndrome (OR 6.79), family history (OR 4.6) and FBS (OR 3.98). High densitiy lipid (HDL) was found to have protective role (OR 0.36) in AN. Conclusion: Findings strongly support that patients with AN are at higher risk for having metabolic syndrome with all components than those without AN. Nepal Journal of Dermatology, Venereology & Leprology, Vol.14(1) 2016, pp.37-43